Work Family Conflict: Tantangan Komitmen Organisasi Dosen Wanita - Rahmawati, Sisca Dian; Alviola, Sharen; Lamidi, Lamidi (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2024)
Female lecturers often carry dual roles, both as working mothers and as homemakers responsible for childcare. During the COVID-19 pandemic, the challenges of balancing work and family roles have intensified. Organizational commitment is not only reflected in lecturers’ involvement with their institutions but also in their ability to remain present and contribute to achieving organizational goals. However, many female lecturers working from home experience work-family conflict, making it difficult to balance professional and domestic responsibilities. This study aims to examine the effect of work-family conflict on the organizational commitment of female lecturers working from home during the COVID-19 pandemic. The research employed a non-experimental quantitative design with a causal method, using a population study of 31 female lecturers at the National Institute of Technology. Data were analyzed using multiple regression. Work-family conflict was measured using the scale by Carlson & Kacmar adapted by Kuntari (2014), while organizational commitment was measured with a tool developed by Ingarianti (2015). The findings indicate that work-family conflict significantly affects organizational commitment among female lecturers working from home, with an R Square value of 0.581, demonstrating an influence of 58.1%.